2012
DOI: 10.1080/1359432x.2012.690399
|View full text |Cite
|
Sign up to set email alerts
|

Setting the tone: Early interaction patterns in swift-starting teams as a predictor of effectiveness

Abstract: Many organizations rely on the functioning of teams. In this study we focus on swift-starting teams-that is, ad hoc teams formed for immediate task performance, such as emergency or rescue teams or aviation crews, with highly trained members who have generally not previously worked together as a team. Previous research suggests that teams develop task performance capability over time, but that stable patterns of interaction in teams emerge very quickly. We suggest that these interaction patterns help swift sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 59 publications
5
123
0
Order By: Relevance
“…These results illustrate the limitations of standardized response patterns and highlight the importance of team adaptability. With emphasis on early interaction patterns in swift-starting teams as a predictor of effectiveness, Zijlstra (2012) reported that the effective teams exhibited patterns that were more stable in duration, more stable in complexity, and more reciprocal as compared to those of less effective teams. Borrie et al (2002) published a paper on temporal pattern analysis and its applicability in sports.…”
Section: T-patterns In Human Behaviormentioning
confidence: 99%
“…These results illustrate the limitations of standardized response patterns and highlight the importance of team adaptability. With emphasis on early interaction patterns in swift-starting teams as a predictor of effectiveness, Zijlstra (2012) reported that the effective teams exhibited patterns that were more stable in duration, more stable in complexity, and more reciprocal as compared to those of less effective teams. Borrie et al (2002) published a paper on temporal pattern analysis and its applicability in sports.…”
Section: T-patterns In Human Behaviormentioning
confidence: 99%
“…One research questions pertaining to phases in meetings concerns the issue of emergent social influence over time. For example, it remains to be seen whether emergent social influence in meetings takes place early on, related to the notion of "setting the tone" for specific interaction patterns (Zijlstra, Waller, & Phillips, 2012). Moreover, meetings research has yet to explore whether social influence fluctuates and changes, with different meeting attendees taking on the leadership roles over the course of a meeting.…”
Section: Future Research Ideasmentioning
confidence: 99%
“…Studies on trust in emergency response are 'scant' [88], however trust is imperative to good teamwork [227,153,213,68], performance [172], and enhanced group decision-making processes [53]. Without trust, collaboration becomes di cult; work is unnecessarily rechecked, people work independently and fail to delegate [53].…”
Section: Trustmentioning
confidence: 99%
“…On the flight deck it is the leader's responsibility to 'establish the social climate in which crewmembers are encouraged and expected to provide and receive information' [92, p. 125]. The communication climate in an aircraft is developed by the pilot briefing [153], and in swift starting teams, the tone of the first few moments establishes this [227]. Behaviours that can reduce the likelihood of people contributing include being treated in a rude manner [209] or being challenged too directly [153].…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation